Application Of Therapeutic Communication Based On Peplau's Theory On Medication Adherence Of Mentally Ill Patients At Soeprapto Hospital, Bengkulu Province In 2025 - Zubiyo, Ahmad; Herniati, Dilfera (Jurnal Kesehatan Mitra Sekawan, 2026)
Mental disorders are conditions characterized by changes in thoughts, emotions, and behaviors that interfere with a person’s ability to function in daily life. One of the main issues commonly found in patients with mental disorders is non-adherence to medication, which can lead to relapse and decreased quality of life. This study aims to determine the effect of therapeutic communication based on Peplau’s theory on medication adherence among patients with mental disorders.This research used a case study method with a qualitative approach involving two patients at Soeprapto Mental Hospital, Bengkulu Province. Data were collected through interviews and observations of the implementation of therapeutic communication performed by nurses over a two-day intervention period. The results of the study showed that both patients experienced improved understanding and increased medication adherence after the therapeutic communication intervention.It can be concluded that the application of therapeutic communication based on Peplau’s theory is effective in improving medication adherence among mental disorder patients through interpersonal relationships, education, and emotional support provided by nurses.